2011
DOI: 10.1155/2011/637395
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of MWCNT Reinforcement on the Strain Hardening Behavior of Ultrahigh Molecular Weight Polyethylene

Abstract: We have investigated strain hardening behavior of ultrahigh molecular weight polyethylene (UHMWPE) reinforced with 2.0 wt% loading of multiwalled carbon nanotubes (MWCNTs). A solution spinning process was used to produce neat and MWCNT-reinforced filaments of UHMWPE. Tensile tests of filaments showed 62% and 114% improvement in strength and modulus, respectively. Strain hardening tests on filaments revealed spectacular contribution by MWCNTs in enhancing strength and modulus by more than one order of magnitude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 37 publications
2
14
0
Order By: Relevance
“…Amongst all the loadings, a 0.5% loading has the minimal impact on the mechanical properties. Similar phenomenon have been observed during CNT inclusion in polyethylene-based polymer systems [34,35] where 2 wt. % of CNT loading was found to be effective.…”
Section: Tensile Testingsupporting
confidence: 81%
“…Amongst all the loadings, a 0.5% loading has the minimal impact on the mechanical properties. Similar phenomenon have been observed during CNT inclusion in polyethylene-based polymer systems [34,35] where 2 wt. % of CNT loading was found to be effective.…”
Section: Tensile Testingsupporting
confidence: 81%
“…In several reports, mechanical properties such as fracture toughness, tensile strength, and elastic modulus of polymer‐based fibers have shown to increase with the addition of carbon nanotubes . These improvements are commonly attributed to effective interfacial adhesion and stress transfer between CNT and the polymer matrix.…”
Section: Introductionmentioning
confidence: 99%
“…In studies where the MWCNT dispersion was more effective with respect to mechanical properties, the Young's modulus generally increases linearly with the MWCNT concentration and the elongation at break and ultimate tensile strength decrease in a nonlinear way . Mahfuz et al found that a more efficient distribution of the MWCNT from solution spinning of UHMWPE filaments with MWCNT leads to an increase in Young's modulus and ultimate tensile strength, with still decreased elongation at break . Reduced elongation at break and tensile strength at break are most likely strongly affected by interaction of the MWCNT with the matrix and the MWCNT agglomerates that are already present in the decorated powder (stress concentration).…”
Section: Resultsmentioning
confidence: 99%